Development and validation of a defect detection and repair method for half grouted sleeve connection. (December 2022) - Xie, Linlin; Wang, Xinyu; Yang, Cantian; Jiang, Yonghui; Liu, Qianmin; Miao, Qisong; Chen, Xi
Abstract: Connection performance of grouted sleeves in precast concrete (PC) structures is a critical issue. This research addressed the widely observed insufficient grouting problem of grouted sleeve connections (GSCs). A defect-detectable and repairable half-grouted sleeve (DDRHGS) was developed, and a quantitative detection and repair method, as well as associated endoscopic equipment, was recommended. The detectability and repairability of the DDRHGS were then validated through laboratory tests and field work in real engineering practice. Subsequently, to further investigate the effect of grouting defect ratios on the tensile performance of the DDRHGS and verify the connection performance after repair, uniaxial tensile tests were conducted on 26 groups with 78 GSCs, which included GSCs with and without defects, as well as repaired GSCs. The influences of the rebar diameter, defect ratio, and repair material on the failure mode and mechanical characteristics of the GSCs were investigated. The test results indicated that the defect ratio significantly affected the connection performance of GSCs. A high defect ratio led to bar slip instead of the expected bar fracture observed for the specimens without defects, and the strength and deformation capacities of such specimens could not meet the requirements of the codes. Approximately identical failure modes and mechanical characteristics were observed between the 48 repaired specimens and specimens without defects, thus conclusively verifying the feasibility, necessity, and reliability of the defect detection and repair method for GSCs.